Etika Ekonomi dalam Hadis Nabi: Landasan Moral bagi Keadilan Distribusi - M. Idris (IAIN Langsa, 2026)
This study aims to analyze economic ethics in the Prophet’s hadith as a moral foundation for distributive justice and to examine their relevance in addressing contemporary economic inequality. The research employs a qualitative library research method using a descriptive-analytical approach to examine hadiths related to economic ethics and distribution, as well as relevant scholarly literature. The findings indicate that the Prophet’s hadith contains fundamental ethical principles that emphasize distributive justice, the social function of wealth, and moral responsibility in economic activities. These principles remain highly relevant as normative guidelines for developing a fair and socially just distribution system, while also bridging the gap between Islamic ethical ideals and contemporary economic realities.